Murder in the basement : a Roger Sheringham case - Berkeley, Anthony, 1893-1971 (Roger Sheringham Cases, 2001)
A ROGER SHERINGHAM MYSTERY.Roger and Molly Dane have something of a surprise in their new house.When Roger explores the basement on return from their honeymoon, he discovers something odd with the flooring.Hoping to find buried treasure, he digs up the body of a woman instead.Chief Inspector Moresby and Roger Sheringham are then left with the task of discovering who the lady was, how she came to be there, and who shot her in the back of the head.